Electrical Post Fire as Cause of Fire Incidents in Region VI, Philippines - Kenneth Occeno (Philippine Association of Institutions for Research, Inc., 2016)
The devastating electrical fire incidents affect the economy of the country, and it is essential to answer this problem. The intention of the study is to determine the origin of the electrical fire and recommend for possible solutions. The study sought to find out the causes of electrical fire incidents in Region VI that can be used as a guide for future research and policy guidelines relevant to prevention activities. Descriptive method of research, employing frequency count and mean was used in the study. Statistical Package for Social Science was used to generate and analyze the data. The result showed that the number one cause of electrical fire incidents in Region VI was electrical post-fire. Aklan had the highest rate of electrical fire incidents caused by short circuit. Antique had the highest rate of electrical fire incidents caused by overheat while Iloilo and Negros Occidental had the highest rate of incidents caused by electrical post-fire. The structures involved in electrical fire incidents were electrical posts, residential buildings, commercial buildings, vehicles, and other structures. Furthermore, other appliances had the highest involvement followed by electric fans, ceiling fans, flat irons, and electric water heaters. The electrical post-fire and short circuit are mostly the causes of electrical fire incidents.